The impact of health volunteering of radiology students on improving their self-skills and practical capabilities in the Kingdom of Saudi Arabia - Alzain, Amel F.; Elhussein, Nagwan; Hamd, Zuhal Y.; Fadulelmulla, Ibtisam Abdallah; Omer, Awatif M.; Alotaibi, Ahoud; Alsuhaymi, Amani; Aljohany, Maram; Alharbi, Najwa; Ahmed, Amna Mohamed; Hussien, Rehab; Elamin, Badria Awad; et al. (Frontiers in Medicine, 2024)
Volunteering is a beneficial activity with a wide range of positive outcomes, from the individual to the communal level. In many ways, volunteering has a positive impact on the development of a volunteer's personality and experience. Our study aims to evaluate the impact of health volunteering on improving the self-skills and practical capacities of students in the western region of the Kingdom of Saudi Arabia. Materials and Methods: The study was a descriptive cross-sectional electronic web-based survey that was submitted on a web-based questionnaire, 183 students answered the survey then the data was analyzed using SPSS. Results: This study shows that 95.6% of participants agree and strongly agree that the health volunteering experience was a useful experience, 2.7% of the participants neither agree nor disagree, and 1.6% disagree and strongly disagree. Regarding the distribution of the participants on skills learned from volunteering experience, the largest proportion of student volunteers in the health sector 36.1% acquired